Jesus followers in the Roman Empire - Duff, Paul B., 1952- (Grand Rapids, Michigan : William B. Eerdmans Publishing Company, 2017)
"When Jesus of Nazareth began proclaiming the kingdom of God early in the first century, he likely had no intention of starting a new religion, especially one that included former pagans. Yet a new religion did eventually develop -- one that not only included non-Jews but was soon dominated by them. How did this happen? Jesus Followers in the Roman Empire by Paul Duff offers an accessible and informed account of Christian origins, beginning with the teaching of Jesus and moving to the end of the first century. Duff's narrative shows how the rural Jewish movement led by Jesus developed into a largely non-Jewish phenomenon permeating urban centers of the Roman Empire. Paying special attention to social, cultural, and religious contexts--as well as to early Christian ideas about idolatry, marriage, family, slavery, and ethnicity --Jesus Followers in the Roman Empire will help readers cultivate a deeper understanding of the identity, beliefs, and practices of early Christ-believers"--
Section one. Setting the stage. Hellenistic culture, Jewish religion, and Roman power -- The early years of the Jesus movement -- From idols to a living and true God -- Section two. Inside the movement. No longer Jew or Greek -- No longer male and female -- No longer slave or free -- Section three. Accommodation and resistance. One in Christ Jesus -- Unstained by the world.
Includes bibliographical references (pages 247-250) and indexes.
Keywords: Church history -- Primitive and early church, ca. 30-600.; Christian life -- History -- Early church, ca. 30-600.; Christianity and other religions -- Judaism